The Heterotrophic Dinoflagellate Crypthecodinium cohnii Defines a Model Genetic System To Investigate Cytoplasmic Starch Synthesis - Deschamps, Philippe (American Society for Microbiology (ASM), 2008)
The nature of the cytoplasmic pathway of starch biosynthesis was investigated in the model heterotrophic dinoflagellate Crypthecodinium cohnii. The storage polysaccharide granules were shown to be composed of both amylose and amylopectin fractions with a chain length distribution and crystalline organization very similar to those of green algae and land plant starch. Preliminary characterization of the starch pathway demonstrated that C. cohnii contains multiple forms of soluble starch synthases and one major 110-kDa granule-bound starch synthase. All purified enzymes displayed a marked substrate preference for UDP-glucose. At variance with most other microorganisms, the accumulation of starch in the dinoflagellate occurs during early and mid-log phase, with little or no synthesis witnessed when approaching stationary phase. In order to establish a genetic system allowing the study of cytoplasmic starch metabolism in eukaryotes, we describe the isolation of marker mutations and the successful selection of random recombinant populations after homothallic crosses.